SIMULATED ANNEALING APPROACH FOR UNIVERSITY TIMETABLE PROBLEM - R. Kristoforus J. Bendi; Hadi Junaidi (Jurnal Ilmiah Matrik, 2019)
Abstract : University Scheduling is a way of allocating students, lecturers, and rooms, which is used for lectures in the available time slots. The common problems are that a lecturer is scheduled in the same time slot, or several courses are scheduled in the same room and the same time slot. For this reason, scheduling needs to be made in such a way that it can optimize the use of resources. We use simulated annealing as an approach to solve that problem. The results showed that the higher the initial temperature value used and the greater the iteration value would reduce the violation constraints in scheduling problems.